La médiation de l'interaction pédagogique sur une plateforme de visioconférence poste à poste - Tatiana Codreanu; Christelle Combe Celik (ALSIC: Apprentissage des Langues et Systèmes d'Information et de Communication)
This article describes the instructional practices of two different populations of online tutors in a multimodal environment: trainee teachers and experienced teachers. They participated in a project using a desktop videoconferencing platform designed for delivering online language courses. Through micro-analysis of a task in the configuration that places a tutor in front of two students, we try to observe how the tutors engage and regulate the discourse of learners. We study the use of the various textual communication tools and of the webcam. We discuss the qualitative findings of the study in order to highlight the semio-pedagogical skills and the ethos of the online tutors.